SOSIALISASI PENGENALAN POTENSI SUMBERDAYA KELAUTAN DENGAN PENDEKATAN BIOPROSPEKSI KELAUTAN KEPADA MASYARAKAT PESISIR LHOK BUBON ACEH BARAT - Mohamad Gazali (Jurnal Marine Kreatif, 2019)
Coastal and marine resources provide several benefit for increasing the coastal prosperity. Several benefits of coastal and marine resources including food and non food sources and drugs. According to survey that coastal and marine resources that widespread alongside of Lhok Bubon coastal including macroalgae, sea cucumber and mangrove. It is to be benchmark to gain information related the provided of biopharmaca raw material. The empowering community activity was held in April 7, 2019 at the beach of Lhok Bubon Samatiga district West Aceh Regency. The method of activity icluding the survey of coastal and marine resources, the socialization of empowering community and beach clean movement. The activity showed the awareness of coastal community to keep the coastal and marine environment. In other hand, the empowering community activity which the coastal community obtained several informations related the utilization of coastal and marine resources in Lhok Bubon Village Samatiga District West Aceh Regency.